CONSTRUCTION OF KNOWLEDGE ABOUT THE THEME PERFORMANCE EVALUATION OF COMMUNICATION IN PUBLIC ORGANS: AN ANALYSIS OF INTERNATIONAL LITERATURE/CONSTRUCAO DE CONHECIMENTO SOBRE O TEMA AVALIACAO DE DESEMPENHO DA COMUNICACAO EM ORGAOS PUBLICOS: UMA ANALISE DA LITERATURA INTERNACIONAL/CONSTRUCCION DE CONOCIMIENTO SOBRE EL TEMA EVALUACION DE DESEMPENO DE LA COMUNICACION EN ORGANOS PUBLICOS: UN ANALISIS DE LA LITERATURA INTERNACIONAL - Ensslin, Leonardo; Graziano, Luiz Antonio Giardino; Dutra, Ademar; Dezem, Vinicius (Revista ibero-americana de estratégia, 2017)
The goal of this study is to analyze the characteristics of the international scientific researches that approach the fragment of the literature on the subject of Evaluation of Performance Communication in public agencies. The methodology is exploratory, descriptive and quali-quantitative approach and uses as instrument the Knowledge Development Process-Constructivist (ProKnow-C) to define the Bibliographic Portfolio and Bibliometric Analysis. The results highlight: (i) The selection of a Bibliographic Portfolio composed of 29 articles; (ii) The most prominent journals are "Public Performance & Management Review" and "Public Administration Review"; (iii) Among the papers, 63% use performance measurement systems and 37% performance management systems; and, (iv) The majority (55%) is in an evolutionary stage of "transition from operations to the strategic orientations". The adoption of realistic evaluation models is noticeable, obtained in a generic form, without taking into consideration the particularities of the contexts and the actors involved in the decision process.